2009
DOI: 10.1063/1.3207837
|View full text |Cite
|
Sign up to set email alerts
|

Natural versus forced convection in laminar starting plumes

Abstract: A starting plume or jet has a well-defined, evolving head that is driven through the surrounding quiescent fluid by a localized flux of either buoyancy or momentum, or both. We studied the scaling and morphology of starting plumes produced by a constant flux of buoyant fluid from a small, submerged outlet. The plumes were laminar and spanned a wide range of plume Richardson numbers Ri. Ri is the dimensionless ratio of the buoyancy forces to inertial effects, and is thus our measurements crossed over the transi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
(44 reference statements)
3
23
0
Order By: Relevance
“…For example, various alternate scaling relationships have been proposed for the rise velocity of plumes [ Batchelor , ; Whitehead and Luther , ; Griffiths and Campbell , ; Moses et al ., ]. This may in part be because several studies have examined plumes generated by the injection of buoyant fluid [e.g., Olson and Singer , ; Griffiths and Campbell , ; Rogers and Morris , ; Bercovici and Mahoney , ], rather than those generated by a heater (which is closer to the nature of the heating in the mantle). The use of injection systems creates an additional controlling variable, the volume flow rate, and the difference in the source of buoyancy is likely to have a significant effect on the fluid dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…For example, various alternate scaling relationships have been proposed for the rise velocity of plumes [ Batchelor , ; Whitehead and Luther , ; Griffiths and Campbell , ; Moses et al ., ]. This may in part be because several studies have examined plumes generated by the injection of buoyant fluid [e.g., Olson and Singer , ; Griffiths and Campbell , ; Rogers and Morris , ; Bercovici and Mahoney , ], rather than those generated by a heater (which is closer to the nature of the heating in the mantle). The use of injection systems creates an additional controlling variable, the volume flow rate, and the difference in the source of buoyancy is likely to have a significant effect on the fluid dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…He further suggested that the buoyancy of the head increases since the head is fed by the stem as a result of the slower upwards motion of the head compared with the steady stem below it. Since then, much effort has been devoted to understand plume dynamics and to provide scalings for plume ascent velocity [ Whitehead and Luther , ; Shlien , ; Olson and Singer , ; Chay and Shlien , ; Griffiths and Campbell , ; Moses et al ., ; Couliette and Loper , ; van Keken , ; Kaminski and Jaupart , ; Rogers and Morris , ; Davaille et al ., ] or for steady state plume stem structure [ Batchelor , ; Fujii , ; Shlien and Boxman , ; Tanny and Shlien , ; Worster , ; Moses et al ., ; Olson et al ., ; Couliette and Loper , ; Vasquez et al ., ; Laudenbach and Christensen , ; Whittaker and Lister , , 2006b; Davaille et al ., ]. Additionally, plume growth by entrainment of fluid by thermal diffusion, continuous feeding from the source, laminar entrainment of surrounding material at the rear of a leading vortical head has been studied [ Griffiths and Campbell , ; Moses et al ., ; Couliette and Loper , ; Kumagai , ].…”
Section: Introductionmentioning
confidence: 99%
“…In their early stages, the external appearances of autocatalytic plumes are similar to non-reacting, laminar plumes [1,6,7]. This suggests that the interior flow profiles of autocatalytic and non-reacting laminar plumes might be similar, at least initially.…”
Section: Simulated Pinch-offmentioning
confidence: 82%
“…In order to quantify the thermal and compositional contributions to buoyancy separately, we define two Rayleigh-like numbers [25,26]. The thermal and concentration Rayleigh numbers are Ra T = gα T L 3 νD ∆T and Ra c = gα c L 3 νD ∆c, (7) respectively. Here, L is a length scale that we choose to be equal to the diffusive thickness of the reaction front, defined by = √ Dτ , where τ is a reaction time scale.…”
Section: A Dimensionless Scaling Considerationsmentioning
confidence: 99%
See 1 more Smart Citation